2012
DOI: 10.1530/erc-12-0175
|View full text |Cite
|
Sign up to set email alerts
|

Hormone response in ovarian cancer: time to reconsider as a clinical target?

Abstract: Ovarian cancer is the sixth most common cancer worldwide among women in developed countries and the most lethal of all gynecologic malignancies. There is a critical need for the introduction of targeted therapies to improve outcome. Epidemiological evidence suggests a critical role for steroid hormones in ovarian tumorigenesis. There is also increasing evidence from in vitro studies that estrogen, progestin, and androgen regulate proliferation and invasion of epithelial ovarian cancer cells. Limited clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
108
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 195 publications
(125 reference statements)
2
108
0
Order By: Relevance
“…Ovarian cancer is a common disease among women, and is said to be connected to reproductive disorders, age, and hormone) (Merritt and Cramer, 2010;Modugno et al, 2012 (Westin et al, 2013;Coleman et al, 2013).…”
Section: Mapk and Ovarian Cancermentioning
confidence: 99%
“…Ovarian cancer is a common disease among women, and is said to be connected to reproductive disorders, age, and hormone) (Merritt and Cramer, 2010;Modugno et al, 2012 (Westin et al, 2013;Coleman et al, 2013).…”
Section: Mapk and Ovarian Cancermentioning
confidence: 99%
“…A large Swedish study has reported that women who were admitted to hospital for ovarian cysts before the age of 29 were at increased risk of ovarian cancer later in life (Borgfeldt & Andolf 2004). Ovarian cancer risk is consistently reported as being reduced by factors that interrupt ovulation, including use of oral contraceptives, pregnancy or breastfeeding (Modugno et al 2012) as well as tubal ligation with the latter most closely associated with endometrioid tumours (Rice et al 2013). Pooled data from 12 prospective cohort studies in North America and Europe identified 2000 ovarian epithelial cancers in approximately half a million women.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In their 2012 review of the epidemiological evidence that androgens might play a role in development of epithelial ovarian cancers, Modugno et al argued that although some epidemiological evidence supported a role for androgens in development of disease, there were also studies that did not support this assertion (reviewed in Modugno et al (2012)). …”
Section: Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations